Genetic manipulation to identify limiting steps and develop strategies for high-level expression of penicillin acylase in Escherichia coli - Chou, C. P.; Yu, C. C.; Tseng, J. H.; Lin, M. I.; Lin, H. K. (Biotechnology and Bioengineering, 1999)
We have identified the bottleneck steps limiting expression of penicillin acylase (PAC) through comparison of the expression performance for various PAC-expression vectors constructed by genetically modulating the efficiencies of transcription and/or translation of the pac gene. To our knowledge, this is the first report demonstrating that expression of PAC could be limited by various steps, such as transcription, translation, and post-translational steps (i.e, translocation and periplasmic processing), depending on the host/vector systems. Results also indicate that the structure of the wild-type pac gene might not be optimal for direct use in production of PAC using recombinant DNA technology. To improve the gene expression, transcription was enhanced by manipulating certain DNA bases in the pac regulatory region, whereas translation was enhanced by enlarging the spacing between the ribosome binding site and the ATG initiation codon to increase the initiation efficiency. The information is useful in terms of developing genetic strategies for overproduction of recombinant PAC in Escherichia coli. (C) 1999 John Wiley & Sons, Inc. Biotechnol Bioeng 63: 283-272, 1999.